Key Factors Strengthening Disaster Preparedness of Barangay Councils in Rizal, Kalinga - Lumabi, Jonard Cariaga; Bayed, Ehrol; Co, Norman; Balbin, Melanio Jay; Keener, Agpawan; Bayangan, Berlyn (International Journal of Language and Literary Studies, 2025)
This study explored the key factors influencing the disaster preparedness of Barangay Disaster Risk Reduction and Management Committees (BDRRMCs) in Rizal, Kalinga. Using a quantitative descriptive-correlational design, data were gathered from 168 BDRRMC members across 14 barangays to assess compliance with preparedness standards and identify the availability of supporting factors such as training, resources, leadership, and inter-agency support. Results showed that BDRRMCs were generally “Fully Compliant” (grand mean = 4.05), with strong coordination with local government units and well-prepared DRRM plans. However, limitations were found in funding, emergency supplies, and technical training access. Support from LGUs and community participation were the most available factors, while specialized training ranked lowest. Significant associations were found between resource availability and demographic variables, but not by barangay. A surprising moderate negative correlation (r = –0.416, p = .000) was found between the availability of resources and compliance level, suggesting that the presence of resources alone does not ensure preparedness. The study highlights the need for inclusive engagement, capacity-building, and improved resource utilization to enhance disaster readiness at the grassroots level.